2007
DOI: 10.1111/j.1601-0825.2006.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Cells from bone marrow that evolve into oral tissues and their clinical applications

Abstract: There are two major well-characterized populations of post-natal (adult) stem cells in bone marrow: hematopoietic stem cells which give rise to blood cells of all lineages, and mesenchymal stem cells which give rise to osteoblasts, adipocytes, and fibroblasts. For the past 50 years, strict rules were taught governing developmental biology. However, recently, numerous studies have emerged from researchers in different fields suggesting the unthinkable--that stem cells isolated from a variety of organs are capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 63 publications
(71 reference statements)
0
22
0
2
Order By: Relevance
“…Reported mechanisms that could explain the presence of donor DNA in nonhematopoietic tissues are stem cell plasticity, fusion of bone marrow-derived blood cells with recipient cells, horizontal DNA transfer from donor to recipient cells, and contamination with donor leukocytes (36)(37)(38)(39)(40)(41)(42). Although we cannot exclude other mechanisms, our data strongly indicate a very simple source: leukocyte contamination.…”
Section: Discussionmentioning
confidence: 60%
“…Reported mechanisms that could explain the presence of donor DNA in nonhematopoietic tissues are stem cell plasticity, fusion of bone marrow-derived blood cells with recipient cells, horizontal DNA transfer from donor to recipient cells, and contamination with donor leukocytes (36)(37)(38)(39)(40)(41)(42). Although we cannot exclude other mechanisms, our data strongly indicate a very simple source: leukocyte contamination.…”
Section: Discussionmentioning
confidence: 60%
“…Of note, the regeneration of injured or damaged epitheliumlined organs requires the coordination of multiple types of cells, the epithelial, endothelial, mesenchymal, and immune cells [38]. Recent studies have shown that mesenchymal stem cells (MSCs) participate in the regeneration and repair of a variety of diseased epithelial tissues, including injured epithelial layers in skin [39], airway [40], cornea [41], gastric and intestine [42,43], kidney [44], and oral cavity [45]. The mechanisms underlying MSC-mediated regeneration of injured epithelial tissues may involve not only the secretion of various factors with antioxidant, anti-inflammatory, antiapoptotic, or proangiogenic functions, but also the transdifferentiation of MSCs into epithelial-like cells possibly through MET [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, embryonic cells loose these properties as differentiation ensues and growth-promoting signals decline. Adult stem cells are not totipotent, and they can be further classified depending on their origin and differentiation potential 3,4,5,6,7,8,9 .…”
Section: Introductionmentioning
confidence: 99%